2010
DOI: 10.4314/acsj.v17i1.54210
|View full text |Cite
|
Sign up to set email alerts
|

Growth and development of wetland-grown taro under different plant populations and seedbed types in Uganda

Abstract: Taro [Colocasia esculenta (L.) Schott] is a member of the Araceace family that is a staple food for many people in developing countries in Africa, Asia and the Pacific Islands. It is widely grown in Uganda but the extent of its production and consumption is not known, partly because it has been ignored as legitimate crop for research and development (R&D), and it is managed outside the conventional agricultural production, marketing and economic channels. Therefore, there is limited information on many aspects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 8 publications
4
19
0
Order By: Relevance
“…increased during the early growth stages before gradually declining as they approached maturity (Fa'amatuainu, 2016;Noor et al, 2015;Tumuhimbise et al, 2009). Meanwhile; Fig. 1B shows that polymer-coated urea produced optimum CI at 1 MAP, whereas urea produced optimum CI at 2 and 3 MAP.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…increased during the early growth stages before gradually declining as they approached maturity (Fa'amatuainu, 2016;Noor et al, 2015;Tumuhimbise et al, 2009). Meanwhile; Fig. 1B shows that polymer-coated urea produced optimum CI at 1 MAP, whereas urea produced optimum CI at 2 and 3 MAP.…”
Section: Resultsmentioning
confidence: 96%
“…Difference in the time in which taro plants produced their highest number of leaves is probably due to the disparity between the sites such as drainage and soil pH. Literature suggested that taro usually increased its leaves production from 1 to 5 MAP (Faamatuainu and Amosa, 2016;Noor et al, 2015;Tumuhimbise et al, 2009). Table 3 shows the leaf blades, petioles, and corms yield (Mg ha -1 ) of taro plants at three harvest intervals applied with CR and FR N fertilizers.…”
Section: Resultsmentioning
confidence: 99%
“…The corm of taro and tannia plants are sources of starch and dietary fibre and also contain substantial amounts of protein, vitamins and minerals (Ndabikunze et al ., ; Akwee et al ., ). In East African countries, both these aroids are mainly cultivated by smallholder farmers where they play important cultural, economic and nutritional roles (Onwueme & Charles, ; Talwana et al ., ; Tumuhimbise et al ., ; Beyene, ).…”
Section: Introductionmentioning
confidence: 99%
“…The dasheen type is known as magogoya in Zimbabwe, the cormels are usually absent and it is the mother corm which is the main storage organ (Tumuhimbise et al, 2009). In the dasheen types of taro, the corm is cylindrical and large.…”
Section: Magogoya (Dasheen)mentioning
confidence: 99%